2000
DOI: 10.1073/pnas.97.21.11587
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rab GDP dissociation inhibitor α in regulating plasticity of hippocampal neurotransmission

Abstract: Rab GDP dissociation inhibitor ␣ (Rab GDI␣) is a regulator of the Rab small G proteins implicated in neurotransmission, and mutations of Rab GDI␣ cause human X-linked mental retardation associated with epileptic seizures. In Rab GDI␣-deficient mice, synaptic potentials in the CA1 region of the hippocampus displayed larger enhancement during repetitive stimulation, which was apparently opposite to the phenotype of Rab3A-deficient mice. Furthermore, the Rab GDI␣-deficient mice showed hypersensitivity to bicucull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 23 publications
4
54
1
Order By: Relevance
“…The production of GDI-1 protein is critical for vesicular membrane transport in both the endocytic and also exocytic pathways via regulation of Ras-like GTPases of the Rab family proteins (Pfeffer et al, 1995;Martinez and Goud, 1998;Luan et al, 1999;Seabra et al, 2002). Moreover, GDI-1 has an important role in vivo to suppress hyperexcitability of the CA1 pyramidal neurons, which changes the firing properties of the neurons (Ishizaki et al, 2000). Consistent with previous reports demonstrating that MK-801 and memantine stimulate hypothalamic-puituitaryadrenal activity by activating corticotropin-releasing factor or cortocoliberin (CRF) in the hypothalamus (Lee et al, 1994;Zhou et al, 1998), we found the increased transcript levels of CRF after both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The production of GDI-1 protein is critical for vesicular membrane transport in both the endocytic and also exocytic pathways via regulation of Ras-like GTPases of the Rab family proteins (Pfeffer et al, 1995;Martinez and Goud, 1998;Luan et al, 1999;Seabra et al, 2002). Moreover, GDI-1 has an important role in vivo to suppress hyperexcitability of the CA1 pyramidal neurons, which changes the firing properties of the neurons (Ishizaki et al, 2000). Consistent with previous reports demonstrating that MK-801 and memantine stimulate hypothalamic-puituitaryadrenal activity by activating corticotropin-releasing factor or cortocoliberin (CRF) in the hypothalamus (Lee et al, 1994;Zhou et al, 1998), we found the increased transcript levels of CRF after both treatments.…”
Section: Discussionmentioning
confidence: 99%
“…56 RabGDIa-deficient mice revealed a role for this protein in neurotransmitter release and synaptic activity in the hippocampus. 57 More recently, D'Adamo et al 58 have produced a mouse model deficient for Gdi1 and showed that the lack of Gdi1 has an effect on the distribution of Rab4 and Rab5 pools, which are Rab proteins involved in synaptic vesicle exocytosis and that GDI deficiency is associated with a defect in short-term memory. Implication in the regulation of synaptic activity was also proposed for IL1RAP, another X-linked gene involved in MR.…”
Section: Synaptic Structure and Function And Mental Retardationmentioning
confidence: 99%
“…83 In addition, Rab GDIα has an important in Rab3A recycling to suppress hyperexcitability through modulation of presynaptic forms of plasticity in the hippocampus. 84 In the NAc, increased phosphorylation of Rab GDIα may serve as a compensatory mechanism to offset hyperexcitability induced by ionotropic glutamate receptors and increased phosphorylation of NR1 following cocaine self-administration in primates. 24 …”
Section: Cell Signalingmentioning
confidence: 99%